Brucella anthropi infection in a 5-week-old infant - Gupta, Prafful; Rai, Ruchi; Singh, D. K. (International Journal of Contemporary Pediatrics, 2024)
Congenital brucellosis in infants is well described but occurs rarely and very few cases have been reported till now. Acquired brucellosis in young infants has rarely been reported. A 5-week-old infant weighing 3340 gm, presented to the emergency with complaints of fever, abdominal distension, lethargy, and decreased feeding for five days. A clinical diagnosis of septicemia was made. Laboratory parameters were suggestive of septicemia. There was a history of ingestion of unpasteurized buffalo’s milk. Empirical antibiotics started after withdrawing the blood culture. Blood culture came positive for Brucella anthropi. Ultrasonography of the abdomen showed a small abscess in the left iliac fossa measuring 44×38 mm. The antibiotics were changed to piperacillin-tazobactam and amikacin as per the blood culture and sensitivity report. Supportive care was given, and the baby gradually improved. The child was discharged on oral rifampicin and trimethoprim-sulfamethoxazole for 4 weeks and is being followed up and is doing well. Young infants may acquire Brucella infection from breastmilk or ingesting unpasteurized animal milk. Prompt diagnosis and treatment is the key to management. Exclusive breastfeeding is the best way to prevent not only animal milk-acquired Brucella but most other types of infection.